Legal Protection of Candidate Head of Regions in the General Election Process Based on Supreme Court Decision Number 1 P/PAP/2021 - Wisnu Nugraha (Journal of Social Research, 2023)
This writing was written to understand the legal protection of candidates for regional heads in the election process based on Supreme Court Decision Number 1 P/Pap/2021. This study uses the method of literature (library research) and uses laws and regulations as well as decisions as research objects studied. The problems studied in this study are (1) What is the authority of the KPU in carrying out the election process in Indonesia? and (2) What is the legal protection for Regional Head Candidates in the election process based on Supreme Court Decision Number: 1 P/PAP/2021? The conclusions obtained are (1) In carrying out the election process in Indonesia, the KPU is given attributional authority based on Article 13 of Law Number 7 of 2017 concerning General Elections, the KPU which principally plays the role of executing orders issued by adjudication agencies (both judicial and quasi-judicial). The KPU also has the authority to implement decisions made by Bawaslu and DKPP, follow up on Bawaslu recommendations, and implement MK and judicial decisions within the Supreme Court, (2) Legal protection for Candidates for Regional Heads, namely the Panel of Judges who examine disputes using the legal basis of Article 135A paragraph (6) Law Number 10 of 2016. This article is a form of legal protection for candidates for regional heads whose constitutional rights have been harmed and violated as a result of the issuance of a KPU decision in the election process, namely by taking legal action through the Supreme Court. The result of the legal effort can be in the form of an annulment of the KPU's decision, and the KPU's decision is declared null and void.